Exploring the Significance of Pharmaceutical Care in Mental Health: A Spotlight on Cannabis - Claudete da Costa-Oliveira; Michele Lafayette Pereira; Nicole Ferrari de Carvalho; Luiza Aparecida Luna Silvério; Ygor Jessé Ramos; Priscila Gava Mazzola (MDPI AG, 2024)
Although preliminary evidence suggests Cannabis's efficacy in symptom control for anxiety and depression-psychiatric disorders that significantly impact mental health-much remains to be understood about its effects on the central nervous system (CNS) and how to optimize treatment for these disorders. This study aims to conduct a narrative review to evaluate pharmaceutical care in treating symptoms of anxiety and depression alongside Cannabis use, focusing on safety and therapeutic efficacy optimization. We seek to conceptualize anxiety and depression disorders, review evidence on Cannabis use, evaluate the evidence quality, and identify knowledge gaps. Twelve articles were identified, revealing a significant gap in the literature regarding the integration of pharmaceutical care with Cannabis-based therapies, specifically for anxiety and depression. Despite a growing interest in the relationship between Cannabis and mental health, current research is insufficient for a comprehensive understanding. The relationship between Cannabis use and anxiety and depression disorders requires further, more targeted investigations. This study underscores the importance of future research to fill existing gaps, providing informed insights and robust guidelines for the safe and effective use of Cannabis as part of the treatment for anxiety and depression. It is crucial that pharmaceutical care integrates these therapies responsibly to improve the overall well-being of patients.